Potential pitfalls of online foreign language teaching from the perspective of the university teachers - Pikhart, Marcel; Al-Obaydi, Liqaa Habeb (Heliyon, 2023)
In the past two years during the COVID-19 pandemic, nearly all universities had to conduct the courses online, including foreign language learning (FLL) classes. Pre-COVID-19 research into the possibilities of digital FLL seemed very optimistic and promising; however, when real life brought the challenges of online classes, the situation was different. This research focuses on the experience of university foreign language teachers from the Czech Republic and Iraq with their online foreign language classes during the past two years. It attempts to analyse their experience and brings together all major issues and concerns they were able to realise. The methodology is qualitative and the number of participants was 42 university teachers from two countries where guided semi-structured interviews were conducted to collect data. The results clearly show that despite the overoptimistic earlier research - the respondents in both countries were very dissatisfied with the way the classes were conducted for various reasons, such as the lack of adequate training, insufficient methodologies for FLL, the lack of motivation in students, dramatically increased screen time of both students and teachers, etc. The most important suggestions call for an adequate methodology for online foreign language learning and necessary professional training so that the instructors are able to keep pace with unprecedentedly fast development in information technology used in various forms of digital learning.
Keywords: Foreign languages; Foreign language learning; Digital learning; L2 acquisition; Online education; Foreign language teaching; FLL